The Aftermath Of Susie Teoh: Are Parental Rights Supreme? - Yong, Chiu Mei (Journal of Malaysian and Comparative Law, 2019)
This article will highlight the inadequacy of Malaysian law, both statutory and judicial, in the area of parent-child legal relationship of non-Muslims, in the light of worldwide rising consciousness of the need to protect the interests and rights of children. Reference will be made to legal developments in the same area in England, the source of much of Malaysian law on parent-child relationships.